2015
DOI: 10.4238/2015.july.27.3
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 polymorphisms and familial aggregation of liver cancer in Guangxi, China

Abstract: ABSTRACT. The goal of present study was to investigate the relationship between polymorphisms of TGF-β1 and familial aggregation of liver cancer in Guangxi Zhuang, Han, and Yao populations. We conducted a population-based case-control family study of liver cancer in Guanxi, China. A total of 214 individuals from 37 case families were surveyed for polymorphisms in TGF-β1. We genotyped six functional TGF-β1 polymorphisms: rs1800469, rs2241715, rs2241716, rs11466345, rs8105161, and rs747857. Levels of TGF-β1, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Finally, as the incubation time of HTLV-1-associated diseases can be very long and there are no markers that predict disease occurrence, robust studies will require large sample sizes, long follow-up periods or both. Such large population-based family studies have been done for other diseases such as multiple sclerosis in Sweden, systemic lupus erythematosus in Taiwan and liver cancer in China, but not yet for HTLV-1 (Hemminki et al, 2009; Kuo et al, 2015; Wan et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as the incubation time of HTLV-1-associated diseases can be very long and there are no markers that predict disease occurrence, robust studies will require large sample sizes, long follow-up periods or both. Such large population-based family studies have been done for other diseases such as multiple sclerosis in Sweden, systemic lupus erythematosus in Taiwan and liver cancer in China, but not yet for HTLV-1 (Hemminki et al, 2009; Kuo et al, 2015; Wan et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that members of the same family share viral, genetic or environmental factors that increase the risk of associated diseases. Family aggregation studies have proven to be a useful component of the research into diseases such as multiple sclerosis (Gourraud et al, 2011), autoimmune diseases (Cárdenas-Roldán et al, 2013), and cancer (Kiciński et al, 2011; Wan et al, 2015). Evidence from such studies can give new insights in disease mechanisms and improve the quality of diagnosis and counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also described TGF-β1 gene variants in codons 10 and 25 of exon 1 and at the promoter region positions -800 and -509 [11,12]. Among these variants, TGF-β1 -509 C>T variants (rs1800469) have been most frequently examined as a possible genetic factor contributing to HCC susceptibility [13][14][15][16][17][18][19][20][21]. However, these studies have yielded conflicting results.…”
mentioning
confidence: 99%
“…Using the predefined inclusion criteria, 10 out of 86 retrieved articles were qualified for analysis [7, 16, 17, 1925] and the selection process is schematized in Figure 1. As two articles from within included sub-studies according to the co-infection of hepatitis B and C viruses [16, 17], a total of 12 studies were qualified for the association of TGFB1 gene C-509T polymorphism with hepatocellular carcinoma, involving 2809 patients with hepatocellular carcinoma and 4802 cancer-free controls.…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of the 12 qualified studies are shown in Table 1. As for the association of C-509T polymorphism with circulating TGF-β1, there were 4 articles [7, 16, 17, 25] involving 10 independent comparisons and 1986 study subjects. The distributions of circulating TGF-β1 across C-509T genotypes are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%